Optimizing MSME Profitability: The Impact of Production Costs On Operating Profit (Case Study: Cassava Chips MSME at Simpang 3 Sibatu Batu Road) - Desmi Triyanti Purba; Elfina O P Damanik; Mahaitin H Sinaga; Melpi Riska Situmorang (Program Studi Akuntansi Universitas Simalungun, 2026)
This study aims to analyze the influence of production costs on business profits and optimize profitability in Cassava Chips MSMEs (Micro, Small, and Medium Enterprises) located at Simpang 3 Jalan Sibatu Batu, PematangSiantar City. This research utilizes a quantitative method with a descriptive approach and simple linear regression analysis. The population in this study consists of the financial records of the Cassava Chips MSME owners, while the sample includes production cost data and business profit data over a 5-year period. The financial analysis utilized includes profitability ratios: R/C Ratio (Revenue/Cost Ratio), ROI (Return On Investment), and Profit Margins (Gross Profit Margin, Operating Profit Margin, and Return On Equity). The results indicate that production costs have a positive and significant impact on business profits. However, an increase in production costs that is not matched by an increase in selling price causes a decline in profit annually. Furthermore, the profitability ratio analysis shows a decline in financial performance due to rising production costs. The research indicates that efficient cost management is proven, where is accepted and is rejected. It is recommended to implement systematic cost recording, increase efficiency, adjust selling prices, and expand marketing to optimize profitability